2018
DOI: 10.1177/0268355518810259
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of cyanoacrylate closure and radiofrequency ablation for the treatment of incompetent great saphenous veins: 36-Month outcomes of the VeClose randomized controlled trial

Abstract: Objective To evaluate the 36-month efficacy and safety of cyanoacrylate closure for the treatment of incompetent great saphenous veins in comparison with radiofrequency ablation. Methods In this multicenter, prospective, randomized controlled trial, 222 symptomatic subjects with incompetent great saphenous veins were assigned to either cyanoacrylate closure or radiofrequency ablation. The primary endpoint, complete closure of the target great saphenous vein, was determined using duplex ultrasound examination s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
59
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 21 publications
0
59
0
3
Order By: Relevance
“…Several studies have shown that CAC is effective with cumulative occlusion rates comparable to those for EVTA in the early and midterm observations. [3][4][5][6][7][8][9][10] In the first-in-men prospective study by Almeida et al, a 36-month occlusion rate was 94.7 % in 29 out of 38 patients with great saphenous vein (GSV) incompetence and a vein diameter of 3-12 mm. [3] A subsequent multicenter European trial (eSCOPE) presented by Proebstle et al enrolling 70 subjects with GSV incompetence and a vein diameter of 6.6-14 mm showed a 12-month occlusion rate of 92.9 %.…”
Section: Effectivenessmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have shown that CAC is effective with cumulative occlusion rates comparable to those for EVTA in the early and midterm observations. [3][4][5][6][7][8][9][10] In the first-in-men prospective study by Almeida et al, a 36-month occlusion rate was 94.7 % in 29 out of 38 patients with great saphenous vein (GSV) incompetence and a vein diameter of 3-12 mm. [3] A subsequent multicenter European trial (eSCOPE) presented by Proebstle et al enrolling 70 subjects with GSV incompetence and a vein diameter of 6.6-14 mm showed a 12-month occlusion rate of 92.9 %.…”
Section: Effectivenessmentioning
confidence: 99%
“…[12] Comparison with thermal ablation A few RCTs compared CAC with EVTA. [4,6,8] In RCT by Çalık et al including 400 patients with GSV incompetence, CAC was compared with endovenous laser ablation (EVLA) and at 12-month follow-up the occlusion rate was 96.6 % and 94.1 %, respectively. [4] The VeClose multicenter RCT, involving 10 centers in USA and 222 patients with GSV reflux in veins up to 12 mm in diameter has shown that CAC was noninferior to radiofrequency ablation (RFA), because the 36-month occlusion rate for CAC was 94.4 % and for RFA, 91.9 %.…”
Section: Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations